PENGARUH KONSENTRASI FLUOR DAN pH PASTA GIGI TERHADAP PELEPASAN ION LOGAM DARI PERMUKAAN LOGAM PADUAN: EFFECT OF FLUORIDE CONCENTRATIONS AND pH OF TOOTH PASTE ON METAL IONS RELEASED FROM ALLOYS SURFACE - Subhaini Jakfar; Poppy Andriany; Bambang Irawan; Siti Triaminingsih (TALENTA, 2010)
It was reported that fluoride in prophylactic agents can be detriment the oxide layers of CoCr and NiCr alloys used as dental restorations. The aim of this study was to determine the effect of fluoride concentration and pH of some commercial toothpastes in Indonesia on the ions released from CoCr and NiCr alloys surface. 120 specimens of CoCr and NiCr alloys were used in this study (60 specimens for each alloy). All specimens were mounted in resin with one side opened. Each alloy divided into 4 groups, there were 15 specimens immersed into 3 kinds of each commercial tooth paste solution (ratio 1:3) and aquabides as control solution for 1, 6, and 13 days duration,. The metal ions released into tooth paste solutions and aquabides were analyzed by AAS tool. The result of study showed that metal ions released into 3 kinds of commercial toothpastes solutions and aquabides were nickel ions from NiCr alloy only, and it was significant (p<0,05) for each aging duration. Lower pH showed higher influence to ion release than fluoride concentrations, and CoCr alloy had a better passive layer than NiCr alloy.